STRENGTHENING DANCE ARTS EDUCATION THROUGH THE CREATIVE PROCESS OF PERFORMANCE: A NARRATIVE LITERATURE REVIEW OF THE PRE-PERFORMANCE, PERFORMANCE, AND POST-PERFORMANCE STAGES - Miftahul Jannah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Dance performance is a form of artistic work that goes through a complex creative process, beginning with pre-performance, continuing through the performance itself, and followed by post-performance stages. This study aims to describe the series of creative processes involved in dance performance by analyzing research themes, methods used, and findings from previous studies. A qualitative narrative literature review approach was applied to twelve journals indexed in Google Scholar, published between 2015 and 2025. The research themes include the creation of dances based on local wisdom, character building, performance evaluation, cultural preservation, as well as production management and the evaluation of performing arts. Most of the studies employed descriptive qualitative methods with data collected through observation, interviews, and documentation. The analysis shows that the creative process of dance performance is strongly influenced by collaboration among artists, in-depth post-performance reflection, and holistic management that supports the sustainability of artistic works. This study provides both theoretical and practical contributions to the development of contemporary dance, while also identifying opportunities for further research related to innovation and management in the performing arts.